Internalizing Aswaja-based Character Education through School Environment Design and Collaborative Strategy - Aan Widiyono (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2022)
This study explores the internalization process of Aswaja-based character education in an Islamic elementary school in Semarang, Indonesia. This qualitative research with a case study design was accomplished at Imama Islamic Elementary School, Semarang, Indonesia. The study results found three findings. First, the school environment was designed by the various religious activities and programs that shape the religious culture in schools. Second, efforts to integrate Aswaja-based character education values ​​in the learning process. Third, it was a collaborative role between the school, parents, and the community, from socialization and planning to evaluating and monitoring the activities and programs. All three are based on the teachings of Aswaja An-Nahdliyah, which emphasize the values ​​of tolerance (tasamuh), balance (tawazun), justice (i'tidal), and moderation (tasawuth). This condition can reinforce the student's character, referring to Aswaja An-Nahdliyah's teaching. The findings of this study imply that the school needs to develop programs to strengthen student character that refer to religious traditions or other local treasures who live in the community. That way, its design and implementation will become more acceptable to the student and the community while at the same time placing the school as a concrete miniature of social life for students.